Oxygen demand of different of sediment at Semariang Batu - Ng, Chiat Siew (Universiti Malaysia Sarawak (UNIMAS), 2009)
Sediment oxygen demand (SOD) is the oxygen consumption exerted by bottom sediment to the overlying water. The uptake of dissolved oxygen (DO) by sediment is usually attributed to the aerobic decomposition of organic matter by microorganism at sediment-water interface and reaction of oxygen with anaerobic respiration by-products. Because the sediments are repository for decaying organic matter, SOD is often a major contributor to DO depletion in poorly fluxed rivers. Low DO concentrations can be detrimental to fish and other aquatic life in a stream. In this study, SOD20 values obtained at five sampling stations ranged from 0.04 to 0.44 gO2/m2day. The benthic sediment quality was classified as clean to moderately clean base on this range. Organic matter, total phosphorus and total kjeldahl nitrogen were ranged from 10.59 to 26.46%, 287.5 to 1445.83 mg/kg and 508.33 to 1277.08mg/kg respectively. Linear regression analysis had been assessed as well in order to determine the relationship between SOD with organic matter, nutrient content and particle size. Results of the present study supported the hypothesis this study that organic matter and nutrient content were major factors that contributed to oxygen demand within the study site. However, it is also noted that there was a poor correlation between sand percentages and SOD values.